Evaluating megaprojects: From the ‘iron triangle’ to network mapping - Lehtonen, Markku (Evaluation, 2014)
Evaluation literature has paid relatively little attention to the spec ific needs of evaluating large, complex industrial and infrastructure projects, often called ‘megaprojects’. The abundant megaproject govern ance literature, in turn, has largely focused on the so-called ‘megapr oject pathologies’, i.e. the chronic budget overruns, and failure of s uch projects to keep to timetables and deliver the expected social and economic benefits. This article draws on these two strands of literat ure, identifies shortcomings, and suggests potential pathways towards an improved evaluation of megaprojects. To counterbalance the current overemphasis on relatively narrowly defined accountability as the main function of megaproject evaluation, and the narrow definition of proj ect success in megaproject evaluation, the article argues that concept ualizing megaprojects as dynamic and evolving networks would provide a useful basis for the design of an evaluation approach better able to promote learning and to address the socio-economic aspects of megaproj ects. A modified version of ‘network mapping’ is suggested as a possib le framework for megaproject evaluation, with the exploration of the m ultiple accountability relationships as a central evaluation task, des igned to reconcile learning and accountability as the central evaluati on functions. The article highlights the role of evaluation as an ‘eme rgent’ property of spontaneous megaproject ‘governing’, and explores t he challenges that this poses to the role of the evaluator.